Dental Radiology and Osteoporosis: The Importance of Using Radiographic Images to Assess Signs of Osteoporosis in Toothless Elderly - Plauto C. A. Watanabe; Giovani Antonio Rodrigues; Marcelo Rodrigues Azenha; Lílian Tedeschi Ramalli (Research Highlights in Disease and Health Research Vol. 4, 2023)
This study sought to analyse the importance of panoramic and carpal radiographs for the evaluation of edentulous individuals, demonstrating the contribution of different dental radiographic techniques in the detection of patients with signs of osteoporosis. 30 digital panoramic and carpal radiographs of women between 50 and 90 years old. In the panoramic radiographs, the thickness of the mandibular cortex was measured (Mentual Index - MI and Goniac Index - GA), and the morphology of the lower cortex was evaluated (Klemetti classification). In the carpal radiographs, the thickness of the cortices of the 2nd, 3rd and 4th metacarpals was measured (Metacarpal Index - IMC - or Nordin Index). The average age of the individuals was 68.43 years. In the analysis of the cortical thickness of the panoramic radiographs, the mean values of the mental index (MI) and the gonial index (GI) referring to the age group of 50 to 59 years had values considered within the normal range (? 3.1mm and ? 1.2mm , respectively). For the analysis of cortex morphology, group C3 corresponded to most cases (43.33%). For carpal radiographs, the highest metacarpal index (IMC) values were found in the younger age group (50-59 years). Finally, there was a positive correlation between age and quantitative (MI, GA, IMC) and qualitative (Klemetti analysis) assessment indices on panoramic and carpal radiographs.